Lumberjanes : Beware the kitten holy, vol. 1 - Stevenson, Noelle; Ellis, Grace; Allen, Brooke A.; Watters, Shannon; Laiho, Maarta; Aiese, Aubrey (Los Angeles, CA. Boom!, 2015)
The story follows a group of girls named Mal, Ripley, Molly, April, and Jo spending summer at a scout camp, and the strange creatures and supernatural phenomena they encounter there.
volume 1. Beware the kitten holy
Volume 1 "Originally published in single magazine form as LUMBERJANES No. 1-4" ; Volume 2 "Originally published in single magazine form as LUMBERJANES No. 5-8" ; Volume 3 "Originally published in single magazine form as LUMBERJANES No. 9-12" ; Volume 4 "Originally published in single magazine form as LUMBERJANES No. 13-16" ; Volume 5 "Originally published in single magazine form as LUMBERJANES No. 17-20"--Copyright page.
Keywords: Teenage girls -- Comic books, strips, etc; Camps -- Comic books, strips, etc; Monsters -- Comic books, strips, etc; Comic books, strips, etc. -- United States; Teenage girls -- Fiction; Camps -- Fiction; Monsters -- Fiction; Cartoons and comics